A descentralização municipal do Rio de Janeiro contribuindo para a revitalização da vida cultural dos bairros e visando à dinamização do desenvolvimento sócio-econômico - Sampaio, Angela Maria Marques (2000)
The present work deals with the viability of a public policy that regards the municipal decentralization in the Cultural field. In the dawn of the Third Millenium, adapting world wide spread policies, Brazil is going through a State Reform. In the current scenario, the strengthening of local power as well the decentralization of municipal administration are the surest keys to the implementation of public policies. The present work proposes inventive initiatives that, contemplating Brazilian reality, valorize talents, reduce needless costs, provide constant increment of public and audience, spread Culture and the popular access to it. The models to be adopted should not only answer the Art and Culture professional classes' demands but also allocate public resources in order to boost Rio de Janeiro City communities' culturallevel. The development of new talents - whether popular or erudite - allied to the valorization of Brazilian folklore and popular art should be enduring political administrative strategies in Rio de Janeiro City. As a matter of fact, the implementation of a Cultural policy that is both decentralized and job/revenue increasing oriented will certainly contribute to reduce Rio's social problems.